ChemInform Abstract: Pd(OAc)2/PPh3‐Catalyzed Desulfonylative Homocoupling of Arylsulfonyl Chlorides. Issue 39 (September 2015) - Zhao, Qiao; Chen, Liangshun; Lang, Hongyue; Wu, Shengying; Wang, Limin
Abstract Biaryls (II) are conveniently synthesized by title reaction in good to excellent yields using silver carbonate or silver oxide as oxidant.